Knowledge, attitude, practices, and perceived barriers to using point-of-care ultrasound by Asian primary care physicians - a mixed method study - Amy Pui Pui Ng; Kiki Sze Nga Liu; Zoey Cho Ting Wong; Zoe Ho Wai Tang; Eric Yuk Fai Wan; Esther Yee Tak Yu; Man Chi Dao; Chun Yu Wu; Tai Pong Lam (BMC, 2024)
Abstract Background Although research shows that point-of-care ultrasound is helpful in primary care, there is little research on point-of-care ultrasound use and the barriers to its use in Asia. This study estimated the prevalence of primary care physicians using point-of-care ultrasound in Hong Kong and assessed their perceived knowledge, attitude, practices, and barriers to using point-of-care ultrasound. Study design This was a mixed-method study: cross-sectional survey, followed by semi-structured interviews. Primary care physicians who were members of the Hong Kong College of Family Physicians and/or were clinical teachers affiliated with the Department of Family Medicine and Primary Care at the University of Hong Kong were invited to participate. Results A total of 330 and 14 completed the survey and interviews, respectively. The prevalence of respondents using point-of-care ultrasound was 22.5%. Perceived knowledge was fair (mean score: 1.9 out of 4; SD: 0.6). The attitudes were mostly positive (mean score: 3.0 out of 4; SD: 0.5). Majority stated that barriers to using point-of-care ultrasound were related to training (90.9%), the competence of point-of-care ultrasound skills (90.2%), and clinical support (89.5%). Qualitative data identified that most participants found point-of-care ultrasound useful; however, participants felt that its use was limited by their competence of point-of-care ultrasound and by factors related to their clinical practice. Conclusions Almost a quarter of respondents are using point-of-care ultrasound with a majority having positive attitudes. They lack confidence in their skills as knowledge is poor but simultaneously find training and clinic support limited.